2018
DOI: 10.12659/msm.909514
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Core Genes and Key Pathways via Integrated Analysis of Gene Expression and DNA Methylation Profiles in Bladder Cancer

Abstract: BackgroundBladder cancer (BC) is the most common urological malignant tumor. In BC, aberrant DNA methylation is believed to be associated with carcinogenesis. Therefore, the identification of key genes and pathways could help determine the potential molecular mechanisms of BC development.Material/MethodsMicroarray data on gene expression and gene methylation were downloaded from the Gene Expression Omnibus (GEO) database. Abnormal methylated/expressed genes were analyzed by GEO2R and statistical software R. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…PENK and PNOC, precursor proteins of enkephalin and nociceptin, respectively, are highly expressed genes in the central neuron system as transmitters to opioid receptor and commonly work in pain transmission and perception. However, the promoter hypermethylation of PENK has been indicated in several malignancies including bladder cancer (54,55), colorectal cancer (56) and pancreatic cells (57,58). In researches, PENK has been reported to be required for apoptosis induction in response to activation or overexpression of p53 and p65 through NF kappa B signaling pathway (59), which is a pathway that is activated in inflammation and enriched in our functional analysis.…”
Section: Discussionmentioning
confidence: 86%
“…PENK and PNOC, precursor proteins of enkephalin and nociceptin, respectively, are highly expressed genes in the central neuron system as transmitters to opioid receptor and commonly work in pain transmission and perception. However, the promoter hypermethylation of PENK has been indicated in several malignancies including bladder cancer (54,55), colorectal cancer (56) and pancreatic cells (57,58). In researches, PENK has been reported to be required for apoptosis induction in response to activation or overexpression of p53 and p65 through NF kappa B signaling pathway (59), which is a pathway that is activated in inflammation and enriched in our functional analysis.…”
Section: Discussionmentioning
confidence: 86%
“…The concentration and purity of total RNA was determined by measuring the absorbance at 260 and 280 nm (A260/A280). Single-strand cDNA was synthesized by reverse transcription with a Superscript II Reverse Transcriptase Kit and oligo dT (12)(13)(14)(15)(16)(17)(18) primers (Invitrogen, Carlsbad, CA, USA) and amplified by RT-PCR with iQ SYBR Green Supermix (Bio-Rad, Hercules, CA, USA). Quantitative PCR (qPCR) was performed using SYBR Green PCR Master Mix (Applied Biosystems) following the manufacturer's instructions.…”
Section: Reverse Transcription Pcr (Rt-pcr)mentioning
confidence: 99%
“…Proenkephalin (PENK) was originally shown to be expressed in the mature nervous and neuroendocrine systems through the opioid pathway and to be involved in the regulation of cell death and survival [10]. PENK has been identified as a key gene in multiple types of cancers [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…We retrieved seven bioinformatics studies for BCa biomarkers based on public database analyses [9,[29][30][31][32][33][34], and we compared the biomarkers in the present study with the ones that were reported in the literature studies. We found that CRYAB and CASQ2 were so far unrecognized as biomarkers in previous studies.…”
Section: Literature Researchmentioning
confidence: 99%
“…The data collection process was undertaken and ended in November 2019. The retrieval criteria were rigorous, filtering with bioinformatics analysis and BCa, only 7 full-text papers were returned [9,[29][30][31][32][33][34]. On the basis of Oncomine database, 5 studies were relevant [35] and we gathered the information of the 14 hub genes from the 5 previous studies.…”
Section: Literature Retrieval and Oncomine Meta-analysismentioning
confidence: 99%